The Involvement of Heavy Metals in the Main Trophic Chains in Agrophytocenoses of the Sterlitamak Region of the Republic of Bashkortostan - M. Zubkova, V.; V. Gaponenko, A.; Yu. Belozubova, N.; V. Reutskaya, V.; R. Khanipova, E. (International Journal of Engineering and Technology, 2018)
The work was aimed at evaluating the involvement of heavy metals in theÂ biogeochemical cycle in the soil-plant system in the setting of agrophytocenoses. The elemental composition of soil and plants was determined by atomic absorption. The sanitary-hygienic and ecological assessment of theÂ condition of soils and plants in the region by heavy metals content has been provided for theÂ first time; for individual items, the health risk of soil contamination and used agricultural products has been assessed. For the first time, background concentrations of priority pollutants in the soil and plants have been found at different sites from contamination sources; theÂ annual average volumes of removal of Cd, Pb, Zn, Cu, Ni, Cr, and Mn from theÂ soil have been established; the antagonistic-synergistic interactions have been revealed at the introduction of macro- and microelements into plants. Â Â